Rancang Bangun Alat Terintegrasi Berbasis Mikrokontroler Arduino Dan GPS Antara Operator Forklift Dengan Material Hangar - Arif Fersian Widyananto; Wahyu Dirgantara; Subairi Subairi (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
This research is conducted due to lack of communication connectivity between forklift operator and material hangar. Aircraft maintenance works continuously. When the hangar technician completely removed an aircraft component then the component shall be sent to the specialize shop by forklift. Unfortunately the forklift is usually not in place and its location is unknown. This will delay the maintenance process and affect the next process. Thus these research is for the communication between two parties, able to do the work coordination, able to track the forklift realtime by software. Hopefully it will speed up the aircraft maintenance process. The components are Arduino Mega 2560 WiFi Built-in, GPS Neo 7M Modul and a server.